Smoldering multiple myeloma: biology, clinical manifestations and management. Issue 3 (23rd February 2022) - Nsiala, Laly; Bobin, Arthur; Levy, Anthony; Gruchet, Cécile; Sabirou, Florence; Gardeney, Hélène; Cailly, Laura; Manier, Salomon; Moya, Niels; Tomowiak, Cécile; Guidez, Stephanie; Leleu, Xavier; et al.
Abstract: Smoldering multiple myeloma (SMM) is a heterogeneous group of asymptomatic plasma cell disorder characterized by the presence of monoclonal protein ≥ 30 g/L and/or 10–60% of bone marrow plasma cells and no evidence of SLiM-CRAB criteria according to the 2014 International Myeloma Working Group (IMWG) recommendations. Once the effort to reclassify SMM with active disease as MM requiring treatment was completed, the need to redefine new high-risk SMM arose. The 20/2/20 and the IMWG risk model with the add-on high-risk cytogenetic abnormalities allow to identify high-risk SMM with 50% risk of progression to MM within 2 years, and therefore might help to propose a better therapeutic approach, either with the goal to « cure » by profoundly debulk the MM with aggressive therapies, or alternatively to restore the immune surveillance like a « delay » strategy with immune-based therapies. The debate is still ongoing but clearly challenges the watch-and-wait standard of care.